Epidemiological evaluation of subclinical mastitis of dairy cows in Greece - THEMISTOKLEOUS, K.; KARAGIANNIS, I.; BOSCOS, C.; PANOUSIS, N.; KIOSSIS, E. (Journal of the Hellenic Veterinary Medical Society, 2020)
Subclinical mastitis, diagnosed by elevated somatic cell count (SCC) in milk, is an important monitoring parameter of dairy cows’ udder health, related to their productivity and welfare. The present retrospective study aims to evaluate the epidemiology of subclinical mastitis (SCM) among the 37 herds of the Holstein Association of Greece participating in the milk quality recording system “ΙΩ”, from the start of 2015 until the end of 2018. The herds’ inclusion criterion was the consistency of monthly SCC recording throughout at least one full year between 2015 and 2018, with a maximum interval of 61 days between two consecutive monthly SCC recordings. Twenty-six herds (8630 cows) in 2015, thirty herds (10763 cows) in 2016, thirty herds (10945 cows) in 2017 and twenty-six herds (9597 cows) in 2018 were included. The prevalence of SCM and chronic SCM, the incidence rate of new cases of SCM, as well as the average somatic cell score and bulk tank milk SCC were determined for each of the four years. The results indicate a progressive deterioration of udder health from the onset of the cow’s productive life until culling. A year-over-year increase in the number of cows with subclinical mastitis led to an overall SCM prevalence of 34.5%, chronic SCM prevalence of 26.9% and a bulk tank milk SCC of 463000 cells/mL, in 2018. The average somatic cell score, a base 2 logarithm of individual cow’s SCC, was found persistently above the subclinical mastitis indicative cut-off in all four years, with a peak in 2018. At herd level, the incidence rate of new SCM cases was 12 new cases / 100 cows / month; the highest incidence rate was observed in the early lactation stage group (1-60 days-in-milk), in all four years, reaching a peak of 31 new cases / 100 cows / month, in 2018. In 2018, prevalence of heifers’ SCM and chronic SCM was23.4% and 16.9%, respectively. Despite the adequate average 305-days milk yield (9608 kg in 2018), the results were indicative of poor udder health status, pointed out by reduced duration of cows’ productive life (less than 3 lactations)and lower milk quality (elevated SCC). The severity and wide spreading of subclinical mastitis in Greek dairy herds highlights the necessity of a national mastitis control program, aiming to improve the productive efficacy, management decisions accuracy and quality of produced milk.